2014
DOI: 10.1139/cjm-2014-0291
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of metallo-β-lactamase among carbapenem-resistant Klebsiella pneumoniae in a teaching hospital in China

Abstract: The aim of this study was to characterize the carbapenemases in carbapenem-resistant Klebsiella pneumoniae (CR-KP) from a Chinese teaching hospital. A total of 40 CR-KPs were screened for the presence of carbapenemases. Minimum inhibitory concentrations were determined by agar dilution. The modified Hodge test was used for the detection of carbapenemase production. Carbapenemase, extended-spectrum β-lactamase, and AmpC genes were detected using polymerase chain reaction (PCR) and sequencing. A conjugation test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…1). Similar results have also been reported in other studies from China [9, 13, 14, 16, 20]. These studies showed that the effects of IMP hydrolase on different carbapenems may be diverse, and therefore, the carbapenem-sensitive phenotype does not mean negative for carbapenemase.…”
Section: Discussionsupporting
confidence: 89%
“…1). Similar results have also been reported in other studies from China [9, 13, 14, 16, 20]. These studies showed that the effects of IMP hydrolase on different carbapenems may be diverse, and therefore, the carbapenem-sensitive phenotype does not mean negative for carbapenemase.…”
Section: Discussionsupporting
confidence: 89%
“…IMP-4 was found among four K. pneumoniae clinical isolates from neonates and three K. pneumonia e isolates from the environment of neonate ICU ( Yu et al, 2012 ). A high prevalence rate (55.0%, 22/40) of MBLs including IMP-4, IMP-8, and NDM-1 was found among CRKP isolates at a tertiary teaching hospital in southeastern China ( Li et al, 2014 ). Co-production of different carbapenamases was also found among clinically important organisms which poses a challenge for infection control ( Karthikeyan et al, 2010 ; Wei et al, 2011 ; Dortet et al, 2012 ; Kumarasamy and Kalyanasundaram, 2012 ; Rimrang et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The major drug resistance gene in China and the United States is KPC, found in >90% of strains, with KPC-2 being the most common. The NDM-1 carrier rate is <10% in China and <5% in America (Deleo et al 2014;Li et al 2014). We suggest that screening be performed to detect other drug resistance genes to better understand the epidemiological trends of drug-resistant strains and provide a theoretical basis for infection control and clinical treatment.…”
Section: Discussionmentioning
confidence: 99%